THE INFLUENCE OF SOCIAL MEDIA INSTAGRAM, TIKTOK, AND WORD OF MOUTH ON THE DECISION TO PURCHASE "MIXUE" ICE CREAM IN SURAKARTA (CASE STUDY OF UNS STUDENTS) - Renata, Triya (Jurnal Manajemen Bisnis dan Terapan, 2024)
This research aims to determine the direct influence of social media Instagram, TikTok, and word of mouth on purchasing decisions for Mixue ice cream in Surakarta. The research strategy used was descriptive and causal. The population produced in this research were students from Universitas Sebelah Maret, Surakarta. The research sample consisted of 39 respondents, namely active UNS students who live in Solo Raya, have bought Mixue ice cream at least once, and have seen content on Instagram, TikTok, and heard about Mixue from other people. The sampling used is a non-probability method and uses a data collection technique, namely purposive sampling. Based on data analysis, this research concludes that social media TikTok and word of mouth have a significant influence on the decision to purchase Mixue ice cream, while social media Instagram does not have a significant influence.